Ethical Dilemma in Diabetes Wound Care: A Literature Review - Zainudin, Harsah Bahtiar; Susanto, Tantut (Babali Publisher, 2025)
Background: One of the main complications of diabetes is diabetic foot ulcer (DFU), which often requires intensive care and involves collaboration between various disciplines. In managing diabetic foot ulcers, several ethical dilemmas arise regarding autonomy, beneficence, non-maleficence, and justice. This review of the literature aims to examine ethical dilemmas in the care of diabetic wounds. Methods: A literature review was conducted to analyze articles published over the last five years (2019–2024). The analysis involved a detailed review of healthcare workers' ethical dilemmas, particularly nurses, in managing diabetic wounds. Results: Nurses are crucial in addressing ethical dilemmas in diabetic wound care. They must have a comprehensive knowledge of diabetic wounds, including their pathophysiology, complications, and treatment options. Nurses must also have strong decision-making skills, allowing them to analyze situations, weigh various factors, and make appropriate decisions. Furthermore, they must maintain effective relationships with patients and their families. Conclusion: Ethical dilemmas in wound care present complex and multidimensional challenges. Nurses must possess adequate knowledge, skills, and support to navigate these situations effectively. By doing so, they can provide high-quality, dignified care to patients while protecting their well-being.